Identifikasi Drug Related Problems Pada Pasien Penyakit Ginjal Kronis Di Rumah Sakit Prof. dr. Chairuddin Panusunan Lubis Tahun 2023 - Rudang, Singgar Ni; Rambe, Rima Elfitra; Annisa, Sheyla (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Chronic kidney disease (CKD) is an abnormality of kidney structure or function, present for â‰¥ 3 months, with implications for health. The high number of medications used by CKD patients can increase the potential for Drug-Related Problems (DRPs) which can interfere with desired health outcomes. This study aimed to determine the occurrence of DRPs in chronic kidney disease patients admitted to Prof. dr. Chairuddin Panusunan Lubis Hospital in 2023. This study was a descriptive retrospective cross-sectional study conducted. Data were obtained from the medical records of CKD inpatients in 2023 (n=51). The sampling technique used was total sampling. The occurrence of DRPs was identified based on the Pharmaceutical Care Network Europe (PCNE) V9.1 classification, which includes problems categories (P1-P3) and causes (C1-C6). There were 28 females (54.90%) and 23 males (45.10%), with an average age of 46.8Â±11.5 years. The highest stage of CKD was stage 5 (78.43%). The most common comorbid condition was anemia (84.31%), with the most frequently used medication being antihypertensives in the Calcium Channel Blocker class (88.24%). Among the 51 medical records, 21 (41,17%) showed the occurrence of DRPs, consisting of 26 Problems (P) categorized under P1. Treatment effectiveness (46,15%) and P2. Treatment safety (53,85%), and 26 Causes (C) categorized under C1. Drug selection (57,69%) and C3. Dose selection (42,31%). Drug-Related Problems (DRPs) occurred in chronic kidney disease patients admitted to Prof. dr. Chairuddin Panusunan Lubis Hospital in 2023.